The Effectiveness of Smart Bucket Box Learning Media in Improving Students’ Learning Outcomes in Islamic Religious Education - Aisyah Zulfa Mazadha; Dian Kusuma Wardani; Nanang Qosim (Al-Mudarris, 2026)
Low student engagement and learning outcomes in Islamic Religious Education (PAI) are often associated with teacher-centered instructional practices that limit students’ active participation and the integration of Islamic values in the learning process. However, the use of interactive and value-based instructional media in PAI remains limited. This study aims to examine the effectiveness of Smart Bucket Box learning media in supporting interactive and value-based learning among students. This study employed a quantitative pre-experimental design using a one-group pretest–posttest involving 32 seventh-grade students at SMP Negeri 4 Jombang. Data were collected through multiple-choice tests administered before and after the implementation of the Smart Bucket Box learning media and analyzed using the Shapiro–Wilk normality test and paired sample t-test. The results showed a significant improvement in students’ average scores from 73.28 in the pretest to 82.97 in the posttest (p < 0.001). The implementation of Smart Bucket Box also created a more interactive learning environment that encouraged student participation during the learning process. These findings indicate that Smart Bucket Box learning media is not only effective in improving cognitive learning outcomes but also contributes to the development of interactive and value-based learning in PAI. This study provides practical implications for teachers in implementing engaging instructional media that integrate cognitive and affective dimensions of Islamic education.